Temperature dependent photochemical cleavage of 2,5-dimethylphenacyl esters - Literák, Jaromír; Relich, Stanislav; Kulhánek, Petr; Klán, Petr (Molecular diversity, 2003)
The study of the temperature-sensitive photochemical release of a carboxylic acid from 2,5-dimethylphenacyl ester is reported. Quantum yields of the benzoate ester degradation in benzene increased from 0.22 at room temperature to 0.28 at 50 degrees C whereas a more significant increase (nearly by a factor of 3) was observed in methanol and ethanol, reaching a high reaction efficiency (0.25) typically found in non-polar solvents. The reaction proceeds predominantly via the triplet pathway and the E-photoenol in the whole temperature range in methanol solution. A higher quantum efficiency in heated methanol is explained by enhancing the E-photoenol population. This picture was partially confirmed by the quantum chemical calculations. The 2,5-dimethylphenacyl chromophore is proposed as an efficient photoremovable protecting group for carboxylic acids in solutions under conventional or microwave-assisted heating for applications in organic synthesis, such as the solid-phase synthesis.
Keywords: Temperature; časové faktory; teplota; fotochemie; chemické modely; chemie organická; Esters; Photochemistry; Spectrophotometry; Models, Chemical; Ultraviolet Rays; Light; mikrovlny; Methanol; magnetická rezonanční spektroskopie; Microwaves; Magnetic Resonance Spectroscopy; spektrofotometrie; ultrafialové záření; Chemistry, Organic; methanol; světlo; Time Factors; estery